Utility‐scale solar photovoltaic power plant emulating a virtual synchronous generator with simultaneous frequency and voltage control provision - Raja Owais; Sheikh Javed Iqbal (IET Energy Systems Integration, 2024)
Abstract Network operators with significant solar photovoltaic (PV) penetration are having difficulty maintaining grid frequency and voltage within acceptable bounds due to the progressive displacement of synchronous machines. Utility‐scale solar PV plants have a huge potential for participation in frequency and voltage regulation since they are linked to the grid through power electronic interfaces with flexible, decoupled control of active and reactive power. A comprehensive control strategy for a utility‐scale solar PV plant is proposed to simultaneously participate in frequency and voltage control without the aid of any energy storage. The frequency response is accomplished by maintaining some active power reserves that enable the PV plant to participate in both over‐ and under‐frequency events. The active power of the PV plant is modulated by operating the PV as a virtual synchronous generator (VSG). Unlike the classic notion of VSG, an intelligent fuzzy‐based technique is employed to adapt the gains of the VSG controller for improved control performance. Additionally, an adaptive droop‐based voltage control mechanism is proposed to control the reactive power reference for the PV plant. The gain of the droop controller is adapted to the varying maximum reactive power capacity of the PV plant. This ensures that the PV system's unused reactive power capability is fully utilised. Through simulation studies, the efficiency of the proposed frequency and voltage control mechanisms is validated under a range of realistic circumstances. The findings show that the suggested control approach can efficiently leverage the PV plants' capacity to handle both frequency and voltage events.